Correlations between photosynthetic heat tolerance and leaf anatomy and climatic niche in Asian mangrove trees. (21st September 2022) - Li, X.; Wen, Y.; Chen, X.; Qie, Y.; Cao, K.‐F.; Wee, A. K. S.
Abstract: Photosynthetic heat tolerance (PHT ) is a key predictor of plant response to climate change. Mangroves are an ecologically and economically important coastal plant community comprised of trees growing at their physiological limits. Mangroves are currently impacted by global warming, yet the PHT of mangrove trees is poorly understood. In this study, we provide the first assessment of PHT in 13 Asian mangrove species, based on the critical temperature that causes the initial damage (TCrit ) and the temperature that causes 50% damage (T50 ) to photosystem II. We tested the hypotheses that the PHT in mangroves is: (i) correlated with climatic niche and leaf traits, and (ii) higher than in plants from other tropical ecosystems. Our results demonstrated correlations between PHT and multiple key climate variables, the palisade to spongy mesophyll ratio and the leaf area. The two most heat‐sensitive species were Kandelia obovata and Avicennia marina . Our study also revealed that mangrove trees show high heat tolerance compared to plants from other tropical ecosystems. The high PHT of mangroves thus demonstrated a conservative evolutionary strategy in heat tolerance, and highlights the need for integrative and comparative studies on thermoregulatory traits and climatic niche in order to understand the physiological response of mangrove trees to climate change‐driven heatwaves and rising global temperatures. Abstract : Asian mangrove trees have high photosynthetic heat tolerance that is correlated with leaf anatomy and climatic niche.